Detox Fashion Sustainable Chemistry and Wet Processing (Textile Science and Clothing Technology,, 2018)
This second volume on detox fashion covers five key aspects relevant to the topic sustainable chemistry and wet processes: Sustainable Chemicals: A Model for Practical Substitution; Sustainable Wet Processing; Coloration and Functional Finishing of Cotton with Plant Extracts; Call for an Environmental Impact Assessment of Bio-based Dyeing-an Overview; and Enzymes: Biocatalysts for Cleaning Up the Textile and Apparel Sector. The book also presents interesting solutions at the level of the supply chain with regard to sustainable chemistry and wet processes.